2014
DOI: 10.12659/msm.891355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SSd Combined with Radiation on Inhibiting SMMC-7721 Hepatoma Cell Growth

Abstract: BackgroundThe aim of this study was to investigate the effects of Saikosaponin-d (SSd) combined with radiotherapy on SMMC-7721 hepatoma cell lines and its mechanism.Material/MethodsSMMC-7721 hepatoma cell lines are selected in our research. With MTT (methylthiazolyldiphenyl-tetrazolium-bromide) method, the effects of SSd and radiation on inhibiting SMMC-7721 cell growth were investigated. We also used transmission electron microscopy (TEM) to observe ultrastructural changes of cells. Colorimetry methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…First, SSd increases the expression of p53 and Bax (Liu & Li 2014 ; Wang et al. 2014a, 2014b ; Yao et al. 2014 ), activates caspases apoptosis pathway, including the activation of caspases-3 and caspases-7 (Chiang et al.…”
Section: Ssdmentioning
confidence: 99%
See 1 more Smart Citation
“…First, SSd increases the expression of p53 and Bax (Liu & Li 2014 ; Wang et al. 2014a, 2014b ; Yao et al. 2014 ), activates caspases apoptosis pathway, including the activation of caspases-3 and caspases-7 (Chiang et al.…”
Section: Ssdmentioning
confidence: 99%
“…Second, SSd decreases the expression of B cell lymphoma 2 (Bcl-2) family proteins (Liu & Li 2014 ; Wang et al. 2014a, 2014b ; Yao et al. 2014 ), suppresses the expression of COX-2, which has been shown to be involved in carcinogenesis (Lu et al.…”
Section: Ssdmentioning
confidence: 99%
“…Saikosaponin D (SSd) is one of the major Saponin components derived from the dried roots of Bupleurum falactum, a traditional Chinese medicine plant. It has been reported that SSd exerts anticancer activities in cervical and lung cancer cells, and hepatocellular carcinoma cells (9)(10)(11)(12). SSd may potentiate tumor necrosis factor (TNF)-α-mediated cell death via suppression of TNF-α-induced nuclear factor (NF)-κB activation, while inducing apoptosis by enhancing the loss of mitochondrial membrane potential (13).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have indicated that SSd exerts anticancer activities in various tumor cell lines (9)(10)(11)(12), the effects of it in central nervous system (CNS) malignant tumors remain unknown. In the present study, the growth potential, proliferation inhibition and apoptosis induction effects of SSd on human U87 glioma cells were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For patients who are not suitable for resection or chemotherapy, radiotherapy is a common effective method; this involves delivering radioisotopes through either a percutaneous or transarterial approach in order to reach the nidus and obtain high tumoricidal activity [62,63]. However, hepatoma cells generally have a lower sensitivity to radioisotopes than other cell types that leads to unsatisfactory curative effects [64]. Radiotherapy also often causes some adverse reactions, such as fever, nausea, chills, poor appetite, and tiredness [65,66].…”
Section: Combination Of Tcm and Radiotherapy For Treatment Of Hccmentioning
confidence: 99%